Identification Formula For Hydroquinone Compound Content In Bulk Body Lotion Cosmetic Preparations Sold On E-Commerce - Ananda Saputra; Septian Maulid Wicahyo; Siwi Hastuti (CV. AFDIFAL MAJU BERKAH, 2026)
The distribution of skin-whitening cosmetics, especially body lotions, through e-commerce platforms is increasing and may contain hazardous ingredients such as hydroquinone. Hydroquinone is a compound that is prohibited for use in cosmetics because it can cause side effects such as dark spots on the skin, allergic reactions, irritation, brain damage, and cancer. This study aims to identify and determine the levels of hydroquinone in body lotion cosmetics sold on e-commerce platforms. This is an observational study with a descriptive approach. A total of three body lotion samples were analyzed qualitatively using a color reaction test with FeCl₃ reagent and thin-layer chromatography (TLC) method, and analyzed quantitatively using ultraviolet-visible spectrophotometry (UV-Vis). The hydroquinone content was determined based on the calibration curve of the standard solution at the maximum wavelength. The results showed that two of the three samples tested positive for hydroquinone in the qualitative test. Quantitative analysis showed that the hydroquinone content in sample 1 was (70.48 ± 0.0044)% and in sample 3 was (67.88 ± 0.0021)%. These levels do not meet cosmetic safety requirements according to the regulations of the Food and Drug Supervisory Agency (BPOM). It can be concluded that there are still body lotions circulating on e-commerce platforms that contain high levels of hydroquinone, so stricter supervision and increased public education regarding cosmetic safety are needed.